Juridical Review of Legal Protection Against E-Commerce Consumers on The Marketplace - Udi Juswanto; Suryanto Suryanto; Yusuf Gunawan (IHSA Institute, 2022)
This study aims to find out and analyze how Law No. 8 can provide legal protection for E-Commers consumers on the Marketplace and to find out and analyze how the legal protection for E-Commers consumers on the Marketplace in the future. The type of research used is normative legal research. So that it focuses on an inventory of positive law, legal principles and doctrines, legal findings in cases in concerto, legal systematics, levels of legal synchronization, legal comparisons, and legal history. This study uses the type of qualitative analysis, which is a study that aims to describe the nature of a particular individual, condition, symptom or group, or to determine the frequency of a symptom, describing the problems that occur related to research. The results show that (1) Legal protection for E-commerce consumers in e-commerce transaction activities on the marketplace is basically an electronic contract engagement activity carried out by two or more parties between business actors and consumers in buying and selling goods and/or services as well as in the form of payment transactions. So that in the process the agreement made is a standard agreement that has a tendency of great risk to consumers.